2009
DOI: 10.1371/journal.ppat.1000273
|View full text |Cite
|
Sign up to set email alerts
|

An Inhibitory Antibody Blocks Interactions between Components of the Malarial Invasion Machinery

Abstract: Host cell invasion by apicomplexan pathogens such as the malaria parasite Plasmodium spp. and Toxoplasma gondii involves discharge of proteins from secretory organelles called micronemes and rhoptries. In Toxoplasma a protein complex comprising the microneme apical membrane antigen 1 (AMA1), two rhoptry neck proteins, and a protein called Ts4705, localises to the moving junction, a region of close apposition between parasite and host cell during invasion. Antibodies against AMA1 prevent invasion and are protec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
204
0
4

Year Published

2011
2011
2019
2019

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 159 publications
(214 citation statements)
references
References 38 publications
6
204
0
4
Order By: Relevance
“…mAbs 1F9 and 4G2 have been shown to inhibit invasion, and this result suggests that invasion is not only blocked by interfering with the binding of AMA1 and RON2 but may also dislodge the bound complex. As the epitope recognized by mAb 4G2 lies adjacent to the hydrophobic pocket in the flexible domain II loop (21,22), these data also suggest that the inhibitory activity of mAb 4G2 could be mediated by stabilizing the domain II loop in an unfavorable conformation for RON2 binding.…”
Section: Resultsmentioning
confidence: 73%
See 2 more Smart Citations
“…mAbs 1F9 and 4G2 have been shown to inhibit invasion, and this result suggests that invasion is not only blocked by interfering with the binding of AMA1 and RON2 but may also dislodge the bound complex. As the epitope recognized by mAb 4G2 lies adjacent to the hydrophobic pocket in the flexible domain II loop (21,22), these data also suggest that the inhibitory activity of mAb 4G2 could be mediated by stabilizing the domain II loop in an unfavorable conformation for RON2 binding.…”
Section: Resultsmentioning
confidence: 73%
“…Previously, Collins et al (22) showed that a mutation in the hydrophobic pocket (Y251A) of AMA1 prevented the binding of AMA1 to a complex of RON proteins in vitro. However, the specific RON protein that binds this pocket was not identified.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Several monoclonal antibodies targeting AMA1 block the interaction with the RON complex and thereby inhibit parasite invasion [40,43,44]. Likewise, several peptides derived from phage-display or from AMA1's binding partner in the RON complex, RON2, are inhibitory [45], establishing the AMA1-RON interaction as a potential therapeutic target [39,46].…”
Section: Ligand Binding To Apical Membrane Antigen 1 (Ama1)mentioning
confidence: 99%
“…AMA1 then relocates to the parasite surface [75] where further processing during invasion leads to shedding of two fragments of 44 and 48 kDa whilst the 22kDa cytoplasmic tail remains in the membrane and is carried into the invaded erythrocyte [76,77]. AMA1 is now known to function in formation of the tight junction through interactions with rhoptry neck proteins [78,79]. This molecule is also expressed in sporozoites where it is involved in hepatocyte invasion [80].…”
Section: Apical Membrane Antigen 1 (Ama1)mentioning
confidence: 99%